OFDM-based time-domain optical MIMO with general-numbered LED configurations - Al-Moliki, Yahya M.; Alresheedi, Mohammed T.; Abas, Ahmad Fauzi; Mahdi, Mohd A.; Ng, Eng Khoon (Springer, 2023)
For optical wireless communication systems with restricted bandwidth, combining multiple-input multiple-output (MIMO) transmission with orthogonal frequency division multiplexing (OFDM) modulation was found to be a highly effective method of boosting system capacity. This paper presents and analyzes two optical OFDM-based MIMO schemes for visible light communications, namely OFDM-based time domain general spatial modulation (TD-GSM) and OFDM-based time domain general spatial multiplexing (TD-GSMP), which utilize general-numbered MIMO configurations of light-emitting diodes (LEDs). These schemes exhibit reduced complexity and provide enhanced spectral efficiency (SE) in comparison to conventional frequency-domain (FD) GSM and GSMP schemes, achieved by transmitting twice the spatial information. Previous research in this area typically employed an even number of LEDs for spatial-based MIMO transmission, represented as , where is the number of spatial bits. However, to enhance SE, this paper introduces schemes that can accommodate a general number of LEDs without the constraint of an even-numbered LED configuration. In indoor environments, several LEDs are already used for illumination purposes, so incorporating additional LEDs for communication does not introduce complexity to the system. To detect both spatial and radiated information, a maximum-likelihood estimation algorithm is proposed. Simulation results demonstrate that, depending on the user’s position, selecting the optimal MIMO configuration is crucial for achieving desired bit error rate (BER) performance and SE requirements. Moreover, as the total number of LEDs increases relative to the active number of LEDs, the modulation order required to transmit signals decreases in order to support a specified SE, resulting in improved BER performance. When all LEDs are active during communication, TD-GSMP outperforms TD-GSM in terms of BER performance. The results also show the superiority of TD schemes over FD schemes in terms of BER performance.